2006
DOI: 10.1093/toxsci/kfj201
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zinc Deficiency Exacerbates Bone Lead Accumulation and High Dietary Zinc Attenuates Lead Accumulation at the Expense of Bone Density in Growing Rats

Abstract: Environmental lead exposure is associated with reduced bone growth and quality, which may predispose to osteoporosis. Zinc supplementation may reduce lead accumulation; however, effects on bone development have not been addressed. Our objective was to investigate the effects of marginal zinc (MZ) and supplemental zinc (SZ) intakes on bone lead deposition and skeletal development in lead-exposed rats. In a factorial design, weanling Sprague-Dawley rats were assigned to MZ (8 mg/kg diet); zinc-adequate control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 37 publications
(61 reference statements)
2
35
1
Order By: Relevance
“…Our results were in agreement with measurements described by Jamieson et al, who stated that the weights of the rats which received treatments with 200 mg/l lead for 3 weeks were significantly decreased. 50) However, rats that were fed with CV recovered their body weights to that of the control within 4 weeks, although food, water consumption and lead exposure levels were not different among the groups. The lead concentration in the tissues (brain, liver and kidney) of the Pb-exposed group was significantly higher than of the control group.…”
Section: Discussionmentioning
confidence: 90%
“…Our results were in agreement with measurements described by Jamieson et al, who stated that the weights of the rats which received treatments with 200 mg/l lead for 3 weeks were significantly decreased. 50) However, rats that were fed with CV recovered their body weights to that of the control within 4 weeks, although food, water consumption and lead exposure levels were not different among the groups. The lead concentration in the tissues (brain, liver and kidney) of the Pb-exposed group was significantly higher than of the control group.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research has investigated the effects of zinc deficiency on bone in the growing rat [4][5][6][26][27][28] ; however, this is the first study to examine bone parameters in 19-week-old young adult rats after consuming zinc-deficient diets for 9 weeks. A novel finding was that BMD was 14% lower in the spine of 9ZD (fed 1-mg Zn/kg diet), but BMD was not altered in the whole body, tibia or femur, or in any of the aforementioned sites in 9MZD rats (fed 5 mg Zn/kg diet), compared to zinc-adequate controls.…”
Section: Discussionmentioning
confidence: 99%
“…Weanling rats are typically used for zinc research because a zinc-deficient state, as determined by a significant reduction in feed intake, body weight gain as well as serum and bone zinc concentrations, can be achieved in 3 weeks with rats fed either severely or marginally zinc-deficient diets [4,5] . In contrast, it takes longer to develop zinc deficiency in older animals because their metabolic zinc requirements for maintenance are low [20] and they have larger bone zinc stores [21] compared to weanling rats.…”
mentioning
confidence: 99%
“…In agreement with previous studies (Cao et al, 2014;Wu et al, 2011b), a negative correlation was found between Pb and Zn, after controlling for gender and age. This could be attributed to the fact that Zn plays an important role in Pb metabolism (Jamieson et al, 2006). However, it is reported that Zn supplementation does not reduce blood lead level (BLL) independently of Zn nutritional status (Roth et al, 2010).…”
Section: Contents Of Heavy Metals and Metalloids In Children's Bloodmentioning
confidence: 99%